Fare paesaggio - Attilia Peano (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
As a consequence of the Cultural Heritage and Landscape Code, Italian Regions are living an intense phase of landscape planning: the new plans (and the conformation of the old ones) need innovations of methodologies and procedures, and, in particular agreements between National and Regional Authorities. The volume presents some results of the Projects of Research of National Interest 2007 “The making of Landscape: from regional planning to local planning and design”. The essays confront the regional experiences, before and after the Code, using common keys for the interpretation, highlighting both the perspectives of innovation and the strength of the traditions, coming from the regional legislation. The second section of the volume focuses on the legislative and planning instruments, providing detailed illustrations.